Material Flow Analysis - Kumar, Sanjeev (IntechOpen, 2021)
This book, titled "Material Flow Analysis," emphasizes the overview of various solid-state joining processes and grain refinement processes where plastic deformation is predominant. In addition, composite processes aimed at strengthening the metal and polymeric materials for various environmental conditions have been incorporated, while advances in the extraction process for purification of tri-n-butyl phosphate (TBP)/inositol hexaphosphate (IP6) have been discussed in detail.